2020
DOI: 10.3390/en13215617
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Flexibility of Electric Vehicles in Germany and California—A Case Study

Abstract: The adoption of electric vehicles is incentivized by governments around the world to decarbonize the mobility sector. Simultaneously, the continuously increasing amount of renewable energy sources and electric devices such as heat pumps and electric vehicles leads to congested grids. To meet this challenge, several forms of flexibility markets are currently being researched. So far, no analysis has calculated the actual flexibility potential of electric vehicles with different operating strategies, electricity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Internet of things devices allow for more detailed data analysis concerning current states of operation and energy consumption over time, which can be used in their optimization. A complete smart-integration of electric vehicle charging [6] and heat pumps [7] leads to flexibilitybusiness cases allowing users earn/save money. In addition to this, smart services are expected to increase the reliability of a network, reduce costs and minimize environmental impact [8].…”
Section: B Smart Services In Local Energy Communitiesmentioning
confidence: 99%
“…Internet of things devices allow for more detailed data analysis concerning current states of operation and energy consumption over time, which can be used in their optimization. A complete smart-integration of electric vehicle charging [6] and heat pumps [7] leads to flexibilitybusiness cases allowing users earn/save money. In addition to this, smart services are expected to increase the reliability of a network, reduce costs and minimize environmental impact [8].…”
Section: B Smart Services In Local Energy Communitiesmentioning
confidence: 99%
“…According to [40], the most important policy tools for promoting electric vehicles are fiscal and infrastructure measures as well as financial incentives for the purchase and support of research and development projects. Research were then conducted on trends, policies, challenges and opportunities in the electric mobility sector in various Countries: Singapore [41], Germany [42,43], California [44,45], Qatar [46], Italy [47], Norway and Canada [48], Greece [49], Australia [50], France [51], Lithuania [52], Japan and South Korea [53], and Pakistan [54].…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The potentials of Building Energy Management System (BEMS) is studied and documented regarding energy-saving [115] and environmental impact [116,117]. Energy flexibility is a crucial term coined to use the building for demand response [118][119][120]. Zhou and Cao [121] intended to study the energy flexibility of the storage systems of a ZEB with a combination of an electric vehicle, but the results showed that the system is already PEB.…”
Section: Smart Energy Managementmentioning
confidence: 99%